Matrix Ansatz, lattice paths and rook placements - S. Corteel; M. Josuat-Vergès; T. Prellberg; M. Rubey (Discrete Mathematics & Theoretical Computer Science, 2009)
We give two combinatorial interpretations of the Matrix Ansatz of the PASEP in terms of lattice paths and rook placements. This gives two (mostly) combinatorial proofs of a new enumeration formula for the partition function of the PASEP. Besides other interpretations, this formula gives the generating function for permutations of a given size with respect to the number of ascents and occurrences of the pattern $13-2$, the generating function according to weak exceedances and crossings, and the $n^{th}$ moment of certain $q$-Laguerre polynomials.